Heterogeneity of Wild Leishmania major Isolates in Experimental Murine Pathogenicity and Specific Immune Response - Kébaïer, C. (American Society for Microbiology, 2001)
Virulence variability was investigated by analyzing the experimental pathogenicity of 19 Leishmania major strains in susceptible BALB/c mice. Twelve strains were isolated from Tunisian patients with zoonotic cutaneous leishmaniasis; seven strains were isolated in Syria (n = 1), Saudi Arabia (n = 2), Jordan (n = 2), or Israel (n = 2). BALB/c mice were injected in the hind footpad with 2 × 10(6) amastigotes of the various isolates, and lesion progression was recorded weekly for 9 weeks. Interleukin-4 (IL-4) and gamma interferon (IFN-γ) production of lymph node mononuclear cells activated in vitro with parasite antigens were evaluated 5 weeks after infection. We show that disease progression induced by different L. major isolates was largely heterogeneous although reproducible results were obtained when using the same isolate. Interestingly, isolates from the Middle East induced a more severe disease than did the majority of Tunisian isolates. Strains with the highest virulence tend to generate more IL-4 and less IFN-γ in vitro at week 5 postinfection as well as higher levels of early IL-4 mRNA in the lymph node draining the inoculation site at 16 h postinfection. These results suggest that L. major isolates from the field may differ in virulence, which influences the course of the disease induced in mice and the type of immune response elicited by the infected host.